2010
DOI: 10.1253/circj.cj-10-0916
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cellular Senescence in Lifestyle-Related Disease

Abstract: Epidemiological studies have shown that age is the chief risk factor for lifestyle-related diseases such as cardiovascular disease and diabetes, but the molecular mechanisms that underlie the increase in the risk of such diseases conferred by aging remain unclear. Recently, genetic analyses using various animal models have identified molecules that are crucial for aging. These include components of the DNA repair system, the tumor suppressor pathway, the telomere maintenance system, the insulin/Akt pathway, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…26,27) P16 and/or p21 deficiency partially prevented the age-induced decline in cell proliferation and tissue function. 28) In this study, we found that Colla corii asini could remarkably decrease p16 and p21 expression. The results suggested that Colla corii asini could modulate age-related gene expression.…”
Section: ) D-galmentioning
confidence: 50%
“…26,27) P16 and/or p21 deficiency partially prevented the age-induced decline in cell proliferation and tissue function. 28) In this study, we found that Colla corii asini could remarkably decrease p16 and p21 expression. The results suggested that Colla corii asini could modulate age-related gene expression.…”
Section: ) D-galmentioning
confidence: 50%
“…It is of note that Vasa et al [17] used the same multiple passage of HUVECs s used in the present study. There is, however, a significant disparity in the rate of senescence in the vascular system depending on local parameters of hemodynamic stress and cellular turnover [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…This might include measures such as telomere length change over time, lens opacities, especially in younger individuals, modifications of insulin-like growth factors and its binding proteins, mitochondrial functional changes, immune marker characteristics, and specific genetic markers of aging [127,137141]. …”
Section: Risk Factors For Ad and Normal Agingmentioning
confidence: 99%